Physiological, Biochemical, and Yield Responses of Linseed (Linum usitatissimum L.) in α-Tocopherol-Mediated Alleviation of Salinity Stress - Abdullah,; Mahmood, Athar; Bibi, Safura; Naqve, Maria; Javaid, Muhammad Mansoor; Zia, Muhammad Anjum; Jabbar, Abdul; Ud-Din, Wasi; Attia, Kotb A.; Khan, Naeem; Al-Doss, Abdullah A.; Fiaz, Sajid (Frontiers in Plant Science, 2022)
Alpha-tocopherol (α-Toc) acts as an antioxidant and prevents from salinity induced cellular oxidation in plants. Current investigation was devised to study the influence of salt (0 and 120 mM NaCl) in linseed (Linum usitatissimum L.) and its alleviation by foliar spray of α-Toc (0, 100 and 200 mg L-1). Seeds of two varieties (Chandni and Roshni) were grown in sand-filled plastic pots with three replicates under Completely Randomized Design (CRD) with factorial arrangement. Salinity remarkably affected the morphology and yield of linseed by declining shoot and root dry weights, photosynthetic pigments (Chl. a, Chl. b, total Chl. and carotenoids), mineral ions (Ca2+, K+) uptake and 100 seed weight, whereas it increased Na+, proline and soluble proteins, peroxidase, catalase and superoxide dismutase in both linseed plants (Chandni and Roshni). However, foliar spray of α-Toc considerably increased growth and yield of linseed varieties by improving dry biomass of shoot and root, photosynthetic pigments, mineral ions, CAT, SOD, POD, proline, soluble proteins and 100 seeds weight under saline conditions. Moreover, α-Toc spray alleviated the stress by decreasing Na+ concentration and enhancing the uptake of K+ and Ca2+. Chandni outperformed Roshni in all growth and physiological parameters of the two tested linseed varieties. 200 mg L-1 α-Toc foliar spray was more in effect to alleviate saline conditions by improving the growth, yield and antioxidant potential of linseed varieties. Therefore, field usage of α-Toc (200 mg L-1) is suggested to enhance the productivity of linseed and other crops in saline soils.